2018
DOI: 10.1039/c7ra12321c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative advantages of Zn–Cu–In–S alloy QDs in the construction of quantum dot-sensitized solar cells

Abstract: one sun irradiation, which was enhanced by 21%, and 82% in comparison to those of CIS/ZnS, and CIS based solar cells, respectively. In comparison to cell device assembled by the plain CIS and core/shell structured CIS/ZnS, the enhanced photovoltaic performance in ZCIS QDSCs is mainly ascribed to the faster photon generated electron injection rate from QD into TiO 2 substrate, and the effective restraint of charge recombination, as confirmed by incident photon-to-current conversion efficiency (IPCE), open-circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…116 Furthermore, they developed a Zn-Cu-In-S alloyed QD sensitizer, exhibiting a PCE of 8.55%. 220 It was demonstrated that alloyed structure is superior to that of the CIS/ZnS core/shell and pristine CIS QDs as sensitizer benefiting from the suppression of charge recombination as well as acceleration of electron injection efficiency. Up to now, this is the best efficiency for CIS QDs based QDSCs.…”
Section: Alloyed Qdsmentioning
confidence: 99%
“…116 Furthermore, they developed a Zn-Cu-In-S alloyed QD sensitizer, exhibiting a PCE of 8.55%. 220 It was demonstrated that alloyed structure is superior to that of the CIS/ZnS core/shell and pristine CIS QDs as sensitizer benefiting from the suppression of charge recombination as well as acceleration of electron injection efficiency. Up to now, this is the best efficiency for CIS QDs based QDSCs.…”
Section: Alloyed Qdsmentioning
confidence: 99%
“…Recently, Zhong et al. investigated the effects of core/shell and alloy structures of CIS QDs on the performance of QDSCs [34] . The results indicated that the Zn‐Cu‐In‐S (ZCIS) alloy QDs prepared by the cationic alloying approach was more effective in improving the QDSCs performance compared to the CIS/ZnS core/shell counterpart, arising from the higher photogenerated electron injection rate and the reduced charge recombination losses.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the performance of different QDs in solar cells, QDSCs based on quinary ZCIS x Se 2− x and quaternary CISSe, ZCIS, and ZCISe QDs were fabricated and evaluated. The photovoltaic performance of cells based on single anion alloyed CISSe QDs was rather poor, with average PCE around only 9–10 % (Table S4), primarily due to the severe charge recombination and slow electron injection rate as demonstrated in previous reports [24, 34] . Therefore, we mainly discuss the performance of QDSCs based on ZCIS, ZCISe, and quinary ZCIS x Se 2− x QDs in the following section.…”
Section: Resultsmentioning
confidence: 92%